Legenda Keramat Madato Kesambi (Kajian Sosiologi Sastra Lisan) - Suntoro Suntoro (STABN Sriwjaya, 2020)
The purpose of this study is to describe the structure, belief, and function of the oral literature of the legend of Keramat Madato Kesambi. This research methodology uses a qualitative approach to the study of sociology of oral literature with data collection instruments in the form of interview guidelines, observation guidelines, and documentation. Testing the validity of the data using triangulation between sources, between methods, and between times. The results of this study indicate: (1) the structure of the legend of the Keramat Madato Kesambi cannot be identified in detail from the introduction, problems, climax, anticlimax, and resolution; (2) the cult of Keramat Madato was not born out of nowhere but was born through accompanying stories such as the story of Tan It Tiaw, the story of the tsunami eruption of Mount Krakatau, the Tragedy of Tangerang 1946, and the deaths of hundreds of pigs; (3) people believe that Madato's figure is a great, people must ask permission at the Keramat Madato before carrying out important events, and the water around the pagoda is not salty even though it is near to the sea as it gets a blessing from Madato; and (4) the sacred legend of Madato Kesambi has several functions, including social control, educational tools, strengthening solidarity, and ratification of cultural institutions.